KEBIJAKAN FORMULASI SISTEM PEMIDANAAN TINDAK PIDANA PENJARA MINIMUM KHUSUS DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Andi Irawan Haqiqi; Jawade Hafidz (Jurnal Hukum Khaira Ummah, 2019)
The formulation of the problem in this research is the formulation policy of the punishment system concerning the special minimum prison crime in the current legal renewal, the obstacles faced in the implementation of the formulation policy of the minimum special prison criminal punishment system in the current legal reform and overcome the obstacles in the implementation of the formulation policy a system of criminal punishment of special imprisonment of special prisons in the upcoming legal renewal. Approach method by writer in this research is normative juridical approach method. Normative juridical legal research is done by analyzing library materials which are secondary data and also called library research law.The result of this research is a special minimum prison formulation policy in the legislation in Indonesia currently spread in various laws and regulations outside the Criminal Code. The formulation of this special minimum prison criminal penalty has a pattern of non-uniform size or weight of punishment between one legislature and another. In relation to the rules and guidelines for the criminal punishment of special minimum prisons are not regulated by the Criminal Code, therefore each law should formulate specific minimum criminal penalty rules and guidelines. In this case it is not only the whole that contains the rules on special minimum criminal, otherwise there is no criminal guidance related to the existence of special minimum prison. The formulation policy of the criminal punishment system on future special imprisonment may be referred to in the Criminal Code concept which contains rules and guidelines on special minimum prison criminal penalties. Concerning with this formulation of the Concept formulates explicitly the existence of special minimum imprisonment in Article 69 paragraph (2). Furthermore, in the comparative study may be used as a reference to strengthen specific minimim prison rules and guidelines, such as the regulation on the Bulgarian Criminal Code which enables the imposition of imprisonment under such special minimum provisions, or to determine a substitute for a criminal offense not specifically threatened, both for imprisonment and fines. Keywords: Formulation Policy, Crime